AN UPDATED REVIEW ON THE APPLICATION OF DENDRIMERS AS SUCCESSFUL NANOCARRIERS FOR BRAIN DELIVERY OF THERAPEUTIC MOIETIES - SASI, SARANYA; JOSEPH, SHARON KUNNATH; ARIAN, ARYA MANGALATH; THOMAS, SACHIN; V. U., AMRUTHA; G. K., ARYA; NAIR, SREEJA C. (International Journal of Applied Pharmaceutics, 2021)
It’s been nearly 100 y of effort to study the organization and role of the blood brain-barrier and still, we strive to find better techniques to overcome this barrier to deliver the drugs to the brain effectively with reduced systemic side effects. The advances in nanotechnology have given newer horizons in achieving this goal since the nano-scaled systems can modify an existing drug to have a high degree of sensitivity to the physiological conditions and specificity to reach the target organ. Among the various nanocarriers, dendrimers owing to their unique physical and chemical characteristics, represent a potential therapeutic tool in biomedical and pharmaceutical science. Dendrimers, an established polymeric nanocarrier system of the time, can deliver both drugs and genetic material and are being extensively studied to target the brain. The surface modification of dendrimers can reduce their innate toxicity problems and increase the therapeutic efficacy of brain disorders. This review article is an attempt to update on the potential of dendrimers explored in the past five years as a drug delivery avenue that can be considered as a promising solution in the management of a wide range of disorders affecting the central nervous system, including neoplastic, degenerative, and ischemic conditions. The following search criteria were used to expand the review article with the keywords dendrimers, novel drug delivery, nanoparticles, site-specific drug delivery etc.